2021
DOI: 10.3390/molecules26144276
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Pharmacokinetic Study of Forchlorfenuron in Adult and Juvenile Rats

Abstract: Forchlorfenuron (CPPU) is a plant growth regulator extensively used in agriculture. However, studies on CPPU pharmacokinetics are lacking. We established and validated a rapid, sensitive, and accurate liquid chromatography–mass spectrometry method for CPPU detection in rat plasma. CPPU pharmacokinetics was evaluated in adult and juvenile rats orally treated with 10, 30, and 90 mg/kg of the compound. The area under the plasma drug concentration–time curve from 0 to 24 h (AUC), at the final time point sampled (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Guidance for Industry [11]. The following performance metrics of the method were examined: specificity, lower limit of detection, lower limit of quantification (LLOQ), linearity, precision and accuracy, recovery, matrix effect (ME), and so on [12].…”
Section: Methods Validationmentioning
confidence: 99%
“…Guidance for Industry [11]. The following performance metrics of the method were examined: specificity, lower limit of detection, lower limit of quantification (LLOQ), linearity, precision and accuracy, recovery, matrix effect (ME), and so on [12].…”
Section: Methods Validationmentioning
confidence: 99%
“…In addition, a study by Gong et al reported that FCF induced cardiac morphology deformation, cardiac contractile dysfunction, and erythrocyte reduction in zebrafish [17,19]. In a more recent study evaluating the potential safety risks of FCF on juvenile rats, Ping et al emphasized the risks of FCF exposure in children after finding that juvenile rats exhibited reduced plasma clearance (CLz) when compared to adult rats [20]. With human populations facing increased exposure to FCF residues through the consumption of fruits and vegetables, these bioaccumulations have also been shown to cause cyto-genotoxicity in human lymphocytes [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Zhu et al [3] stated that CPPU could promote estradiol secretion and adversely affect prepubertal female rats. Furthermore, Ping et al [7] reported that CPPU had more potent effects on juvenile rats than adult rats in a pharmacokinetic experiment. Therefore, it is speculated that CPPU is potentially harmful to adolescent health.…”
Section: Introductionmentioning
confidence: 99%